Model checking of trusted cryptographic module - CHEN Xiao-feng; FENG Deng-guo (Tongxin xuebao)
The formal security analysis was given for the trusted cryptographic module according to the specification of the trusted cryptographic module using model checking tools. The flaws in the AP protocol were pointed and the solution was given. Meanwhile, the framework was proposed for analyzing the security property of the trusted cryptographic module using the model checking tools.